اللواصق وأثرها في بنية الفعل التركيبية والدلالية - الأحمدي، وئام مساعد Alahmadi, Wiam Mosaed (المركز القومي للبحوث غزة, 2017)
يعالج البحث أثر اللواصق في بنية الفعل التركيبية حيث أُقر أن الفعل في العربية لا يتصف بسمة النوع المتجسدة في التأنيث والتذكير, وإنما هذه السمات خاصة بالأسماء وحدها، ووجود علامة تأنيث في الفعل أو انعدامها تدل على تأنيث الفاعل أو تذكيره. أما ما يخص الجمع فهي سمة نحوية ممكنة في الأفعال إذا نُظر إليها باعتبار أنها تحقق مفهوم التكثير والتكرار، لا باعتبار العلامات الملتبسة بالضمائر، فالجمع والتثنية من هذه الوجهة من خصائص الاسم فقط، حيث يكتفي الفعل بدلالة فاعله على هذه السمة. فيما يتبين أن ظاهرة التطابق بين الفعل وفاعله لا تتحقق إلا في سمة الجنس, إذ لا تقبل العربية الفصحى بوجود هذا التطابق في سمة العدد.
The research examined the effect of affixes on the verbs’ synthetic structure, which proved that the verb in Arabic is not affected by Gender, this is the case of nouns only, the existence and non existence of feminine indications in the verb is a reference to the femininity or masculinity of the subject. In relation to plurals it is a grammatical trait contingent if used to achieve the concept of multiplication and repetition, not in consideration of the indications mistaken for pronouns, pluralizing and doubling from this prospect are features to the noun only, the verb relies on the subject in this trait. It appears that the phenomenon of uniformity between the verb and his subject is noticed with Gender indications, but with number indications classical Arabic does not accept this kind of uniformity.
Keywords: اللغة العربية; النحو العربي; اللواصق